PENCEGAHAN HOLISTIK AL-QUR’AN TERHADAP POTENSI KEKERASAN SEKSUAL - Ibrahim; Rosmini; Achmad Abu Bakar (JURNAL SIPAKALEBBI, 2023)
Sexual violence is an important issue that is rife nowadays, not only experienced by women but also in several cases against men. The phenomenon of violence in everyday life often occurs both in the domestic and in the public sphere. The types also vary from verbal, physical to digital sexual violence. The main problem contained in this paper is how the Qur'an declares comprehensive prevention against the potential for violence and sexual harassment. This paper is classified as a qualitative type of library research, in which all of it referred to literature originating from written materials or library research by referring to the Thematic Interpretation procedure as an approach in analyzing the verses of the Al-Qur'an in collaboration with related scientific approaches including sociological and psychological approaches. Within the framework of preventing sexual harassment and violence, the Qur'an teaches several things. First, teaching children about the limits of genitalia that have been regulated in Islam. Second, separating the child's bed. Third, askingfor permission when entering someone else's house or bed, including the parents' room. Fourth, educating yourself to always keep your eyes on. Fifth, recognizing the identity of sexuality. Sixth, educating children not to commit khalwat. Seventh, prohibiting of sexual touch before marriage.